IMPLEMENTASI ALGORITMA FUZZY UNTUK PENILAIAN KEPUASAN NASABAH PNM MEKAR DI PASAMAN - Rahma Yanti; Sela Ramadani; Dina Selvia; Rini Sovia (Smart Education, 2025)
Customer satisfaction assessment is an essential component in improving the service quality of PNM Mekar, a microfinance institution focused on empowering women through ultra-micro financing. Conventional evaluations rely heavily on subjective perceptions, creating a need for a more structured and objective method. This study applies the Fuzzy Logic algorithm to measure customer satisfaction by transforming numerical data into linguistic variables through fuzzification. Annual operational data, including the number of customers and returning customers, were processed using membership functions and fuzzy rules, followed by defuzzification to obtain a crisp satisfaction value. The results indicate that all satisfaction levels fall into the low category, suggesting the need for service improvement. The fuzzy-based model proves effective in providing adaptive, consistent, and realistic satisfaction evaluation.